Sand casting of sheet lead: numerical simulation of metal flow and solidification - Prabhakar, Arun; Papanikolaou, Michail; Salonitis, Konstantinos; Jolly, Mark R. (Springer, 2019)
Sandcast lead sheets are characterised by their superior aesthetic performance and mottled surface. Lead sheet casting is widely used in the construction industry for roofing and flashing applications, while the roots of this process can be tracked back to the Roman times. In this study, two-dimensional Computational Fluid Dynamics (CFD) simulations have been performed to simulate the melt flow and solidification stages of the lead sandcasting process. The effects of process parameters such as pouring temperature, screed velocity and clearance between the screed and the sandbed on the final quality of the lead sheet are investigated. Lead sheet quality has been quantified by measuring the variance and the average value of the final sheet thickness over the sandbed length. The developed CFD model has been validated against experimental results by comparing the time evolution of the lead-sandbed interface temperature against data collected by thermocouples during the real-time process. The numerical results show that all of the aforementioned parameters affect the final quality of the cast product and suggest that superior quality lead sheets can be produced for a range of relatively low values of the pouring temperature and slow strickle motion.
Keywords: Sheet casting; CFD; sheet thickness; Lead